‘Fall to Rise’ : A Quest to Revive Performance of Sri Lanka’s Boutique Hotels in Post-Easter Attack - Ranitha Sachinthana Weerarathna; Nipuni Jayasinghe; Tharuka Ellepola; Nimesh Balasuriya; Eashani Uddeepa; Umasha Kanumale (Journal of Accounting, Business and Management (JABM), 2022)
This study aims to identify the factors influencing the business performance of boutique hotels in Sri Lanka, in particular, those factors that impact the most post-Easter Sunday attacks. Three major factors were identified based on past literature; these were operators’ experience and strategies, financial structure and marketing strategies. During May to July, 2020, data were collected via a questionnaire to respondents, who are owners of 53 boutique hotels. Snowball sampling was used as the sampling technique. Data were analyzed using SPSS stastical software and multiple regression was used to identify the factors that influence the performance of boutique hotels the most. The study findings conclude that the -operator’s previous experience and strategies- is the factor that influences business performance the most. Twelve semi-structured interviews were conducted to investigate/examine how boutique hotels have regained their business performance in the aftermath of the Easter Sunday attack. The analysis revealed that boutique hotels have adopted the local market strategy, the social media marketing strategy, discounts and promotional strategies, the employee lay off strategy and the employee training & development strategy to regain business performance post-Easter Sunday attacks. This study is significant for boutique hotel owners to maximize their profits and for the government to implement better tourism-related policies, to revive Sri Lanka’s tourism industry.